Pharmacological inhibition of DNA-PK stimulates Cas9-mediated genome editing - Robert, Francis (Genome Med, 2015)
BACKGROUND: The ability to modify the genome of any cell at a precise location has drastically improved with the recent discovery and implementation of CRISPR/Cas9 editing technology. However, the capacity to introduce specific directed changes at given loci is hampered by the fact that the major cellular repair pathway that occurs following Cas9-mediated DNA cleavage is the erroneous non-homologous end joining (NHEJ) pathway. Homology-directed recombination (HDR) is far less efficient than NHEJ and makes screening of clones containing directed changes time-consuming and labor-intensive. METHODS: We investigated the possibility of pharmacologically inhibiting DNA-PKcs, a key player in NHEJ, using small molecule inhibitors (NU7441 and KU-0060648), to ameliorate the rates of HDR repair events. These compounds were tested in a sensitive reporter assay capable of simultaneously informing on NHEJ and HDR, as well as on an endogenous gene targeted by Cas9. RESULTS: We find that NU7441 and KU-0060648 reduce the frequency of NHEJ while increasing the rate of HDR following Cas9-mediated DNA cleavage. CONCLUSIONS: Our results identify two small molecules compatible for use with Cas9-editing technology to improve the frequency of HDR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13073-015-0215-6) contains supplementary material, which is available to authorized users.